2013
DOI: 10.1161/hypertensionaha.111.00754
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Angiogenic Factors and Urinary Prolactin as Predictors of Adverse Outcomes in Women With Preeclampsia

Abstract: Preeclampsia is a multisystemic pregnancy-specific disease characterized by endothelial dysfunction.1 This condition develops in 5% to 8% of all pregnant women and remains a major cause of maternal and perinatal morbidity and mortality worldwide. 2,3 Although the cause of this pregnancy-specific syndrome is unclear, accumulating evidence suggests that preeclampsia results from an imbalance between placental proangiogenic and antiangiogenic factors that result in maternal vascular endothelium damage. 4,5 Higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 25 publications
5
40
0
3
Order By: Relevance
“…Furthermore, women with pre‐eclampsia who received pravastatin had a lower baseline sFlt‐1:PlGF ratio compared with women who received placebo. Others have shown that a high sFlt‐1:PlGF ratio is associated with an increased adverse outcome and shortened time to delivery . Our own exploratory analyses confirmed this association, which could explain the slightly longer pregnancy duration following pravastatin treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, women with pre‐eclampsia who received pravastatin had a lower baseline sFlt‐1:PlGF ratio compared with women who received placebo. Others have shown that a high sFlt‐1:PlGF ratio is associated with an increased adverse outcome and shortened time to delivery . Our own exploratory analyses confirmed this association, which could explain the slightly longer pregnancy duration following pravastatin treatment.…”
Section: Discussionsupporting
confidence: 83%
“…10 Contrary to sFlt-1, PlGF is thought to exert a direct proangiogenic function in the maternal circulation, and the levels of PlGF are decreased early in pregnancies later complicated by preeclampsia. 11 The ratio of sFlt-1/PlGF predicts the development of preeclampsia in some, [12][13][14][15] but not all studies. 16 Failure to detect a correlation between an elevated sFlt-1/PlGF ratio and preeclampsia may reflect an imprecise diagnosis of preeclampsia or a separate disease entity; for example, failure of detecting the differential diagnosis of glomerulonephritis.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the regulation and signaling of angiogenic pathways have been showed to contribute to the inadequate blood supply of the placenta in patients with pre-eclampsia [2,3].…”
Section: Introductionmentioning
confidence: 99%